What Are Inclusive Institutions And How Do They Promote Development? - Zokirov Mirzo (Periodica Journal, 2025)
This article explores the nature of inclusive institutions and analyzes their fundamental role in fostering sustainable economic and political development. Inclusive institutions create broad-based opportunities for participation in economic activities, ensure the protection of property rights, encourage innovation, support fair competition, and enable citizens to take part in political decisionmaking processes. The study explains how these institutions strengthen social equity, stimulate long-term economic growth, and enhance political stability by limiting the concentration of power and resources in the hands of narrow elites. Through theoretical insights and comparative examples, the article demonstrates that inclusive institutions are the foundation upon which prosperous, innovative, and democratic societies are built.
Keywords: inclusive institutions; economic development; political participation